Ghosts of the Wild West : Enlarged Edition Including Five Never-Before-Published Stories - Roberts, Nancy, 1924-2008 (Book collections on Project MUSE., 2008)
A new expanded compendium of spine-tingling tales of Western haunts and horrors.